The Brasilia Rules and the rights of the family, children and adolescents. Limitations in the access to justice for children and adolescents in the context of domestic violence - Rodríguez Chávez, Reyler (2022)
This article attempts to describe the main limitations in the access to justice for children and adolescents suffering from domestic violence in which they are direct or indirect victims. In view of the minority of this vulnerable population, they face the obstacle of the absence or impossibility of being legally represented to exercise their rights and their interests, especially when their parents or caregivers are directly involved in acts of domestic violence. As legally recognized persons with full capacity, by desisting or recanting or simply abandoning the pursuit of justice on their own behalf, directly or implicitly affects the vulnerable situation of children and adolescents affected by domestic violence. In this regard, we shall analyze this subject in accordance with the guarantees proposed in the Brasilia Rules, the Convention on the Rights of the Child and other international conventions, as well as the laws of protection in the national legislation, to establish the need to build reinforced guardianship safeguards for the protection of children and adolescents in this situation.